Drying Kinetics and Hygroscopic Balance of Rosemary Leaves (Research, Society and Development, 2020)
The medicinal plants of genus Lippia is used worldwide for its medicinal characteristics. However, there is a need to study the drying kinetics and hygroscopic balance of Lippia gracilis leaves by varying the drying temperature. The objective of this work was to study the drying kinetics of Lippia gracilis as well as to adjust a model among those existing in the literature that best represents the behavior of the sorption isotherm. The rosemary leaves were processed and submitted to drying air temperatures of 40, 50, 60, and 70 ºC in a fixed layer mechanical dryer. For the study of the hygroscopic phenomenon, temperatures of 20, 30, 55, and 70 ºC were used with water activities between 0.11 and 0.81. The model that best represented the drying curves was the Midilli model with an R² of 99.60. The model that best represented the hygroscopic balance curve of Lippia gracilis was that of Sabbah with an R² of 93.33%.